Improving Service Quality Workshop: A Practical Guide for Government Servants - choirisa, Septi Fahmi; Alexandra, Yoanita (Riau Journal of Empowerment, 2023)
Indonesian citizens face scepticism toward government servants in various service departments. This paper aims to synergize the actual needs of society and the transformation of government service. In doing so, the community outreach program conducted several stages, from planning to evaluation with government servants in the district and sub-district of Gading Serpong, Tangerang, Indonesia. A total of 52 participants were involved in this program in an onsite class with fully functional learning tools. As a result, content related to the service is excellent in fundamental knowledge, and quizzes to discover their abilities in handling different customer traits have been successfully delivered effectively. However, this program has time limitations, suggesting that future workshops have complete material prepared to emphasize participants understanding. This theoretical and practical contribution is discussed.